2020
DOI: 10.1016/j.bios.2020.112494
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplex based biosensor: A potential tool for SARS-CoV-2 detection

Abstract: G-quadruplex is a non-canonical nucleic acid structure formed by the folding of guanine rich DNA or RNA. The conformation and function of G-quadruplex are determined by a number of factors, including the number and polarity of nucleotide strands, the type of cations and the binding targets. Recent studies led to the discovery of additional advantageous attributes of G-quadruplex with the potential to be used in novel biosensors, such as improved ligand binding and unique folding properties. G-quadruplex based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 121 publications
1
56
0
Order By: Relevance
“…Previous reports have employed a similar strategy to detect both human and plant viruses (Yang et al, 2017;Kim et al, 2018;Wang et al, 2019), and a recent report has suggested the potential use of DNAzyme sensors for SARS-CoV-2 detection (Xi et al, 2020). We here demonstrate the utility of this approach for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 58%
“…Previous reports have employed a similar strategy to detect both human and plant viruses (Yang et al, 2017;Kim et al, 2018;Wang et al, 2019), and a recent report has suggested the potential use of DNAzyme sensors for SARS-CoV-2 detection (Xi et al, 2020). We here demonstrate the utility of this approach for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 58%
“…. In this way, the RT-LAMP method’s sensitivity for detecting SARS-CoV-2 RNA in clinical samples with CT < 30 was confirmed [ 83 ]. Zhang et al also investigated a colorimetric LAMP biosensor.…”
Section: Biomarkers and Indicatorsmentioning
confidence: 94%
“…Mouse anti-human IgG antibody (MHIgG) and rabbit IgG (RIgG) were used to functionalize LNPs. By dispensing a recombinant nucleocapsid phosphoprotein of SARS-CoV-2 onto a nitrocellulose membrane, the specific IgG of SARS-CoV-2 was captured Anti-SARV-CoV-2 IgG - Reverse transcription loop-mediated isothermal amplification (RT-LAMP) [ 83 ] A two-color RT-LAMP assay protocol was utilized to detect the SARS-CoV-2 N gene in clinical samples. The color of the phenol-red dye was changed within 30 min of the reaction in the presence of positive clinical samples with a CT of less than 30 SARS-CoV-2 RNA (N gene) Cycle threshold (CT) less than 30 Colorimetric Loop-Mediated Isothermal Amplification (LAMP) biosensor [ 84 ] Five LAMP primers sets were designed to detect the SARS-CoV-2 RNA (ORF1a gene and Gene N).…”
Section: Biomarkers and Indicatorsmentioning
confidence: 99%
“…Initially, a combination of computed tomography (CT) scans, next-generation sequencing, Polymerase Chain Reactions (RT-qPCR), ELISA and CRISPR based diagnostic approaches were used to scan and detect SARS-CoV-2 [ 2 , 6 ]. These molecular methods (RT-PCR, CRISPR) are more appropriate than syndromic testing and CT scans for correct identifications of virus [ 7 ]. Though, CT scanners are restricted to bigger hospitals, but cannot differentiate a particular virion from different viruses.…”
Section: Introductionmentioning
confidence: 99%